2022
DOI: 10.3389/fgene.2022.1013858
|View full text |Cite
|
Sign up to set email alerts
|

Using dried blood spot on HemoTypeSC™, a new frontier for newborn screening for sickle cell disease in Nigeria

Abstract: Background: HemoTypeSC is a rapid, point-of-care testing (POCT) device for sickle cell disease (SCD) that traditionally uses the capillary blood from heel stick collected at the point of testing, a procedure that makes mass screening cumbersome and less cost-effective. Using dried blood spots (DBS) on HemoTypeSC could mitigate this challenge. Therefore, this study aimed to determine the feasibility of eluting blood from DBS to read on HemoTypeSC.Methods: DBS and fresh samples from heel sticks were collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Instrumental platforms typically used for such purposes as mentioned in the introduction (e.g., CE, HPLC, or MS/MS) are usually complex and costly. However, in this respect, qPCR-based primary screening for HbS alleles and thus reducing the sample size to a group of specimens relevant to further investigations might be a promising approach to open SCD screening to less complicated and/or inexpensive methods, such as chip-based microelectrophoresis, aqueous multi-phase systems based on cell density measurements, lateral flow immunoassays, or even classical electrophoresis [23,[36][37][38].…”
Section: Plos Onementioning
confidence: 99%
“…Instrumental platforms typically used for such purposes as mentioned in the introduction (e.g., CE, HPLC, or MS/MS) are usually complex and costly. However, in this respect, qPCR-based primary screening for HbS alleles and thus reducing the sample size to a group of specimens relevant to further investigations might be a promising approach to open SCD screening to less complicated and/or inexpensive methods, such as chip-based microelectrophoresis, aqueous multi-phase systems based on cell density measurements, lateral flow immunoassays, or even classical electrophoresis [23,[36][37][38].…”
Section: Plos Onementioning
confidence: 99%
“…A study by Olatunya et al, 2021 found that HemotypeSC had perfect concordance with PCR and 100% accuracy in diagnosing SCD, while Nnodu et al, 2019 reported a sensitivity of 93.4% and a speci city of 99.9% for SCD (26,33). In addition, Okeke, 2022 further demonstrated the feasibility of using dried blood spots with HemotypeSC, with a sensitivity and speci city of 100% compared to the standard test (31). A further study by Adegoke et al 2022,(34) also found high sensitivity of HemotypeSC when compared to alkaline cellulose acetate hemoglobin electrophoresis.…”
Section: Introductionmentioning
confidence: 99%
“… 16 Two of these POC tests, Sickle SCAN and HemoTypeSC, have demonstrated promise and accuracy in high- and low-resource settings and are now being distributed across Africa. 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 These 2 POC tests have not yet been compared directly to one another in a real-world setting and there remains a debate as to whether either of these tests can serve as a standalone diagnostic method for screening infants and newborns in the high prevalence regions of sub-Saharan Africa. In this study, we aimed to evaluate and compare the accuracy of Sickle SCAN and HemoTypeSC with the gold standard IEF as primary diagnostic methods to screen newborns and young infants in Luanda, Angola.…”
Section: Introductionmentioning
confidence: 99%